Tổng hợp và nghiên cứu mối tương quan giữa cấu trúc phân tử với khả năng ức chế ăn mòn kim loại của một số hợp chất axetophenon-aroyl hiđrazon - Vũ, Phương Liên (2016)
Some hydrazones from hydrazides of substituted btenzoic acids with 2, 5 dihidroxyacetophenones have been prepared by the condensation of hydrazides of substituted benzoic acids with 2, 5 dihldroxyacetophenones. The structure of these products have beZn determined by IR,'H-NMR and MS specnoscopiis. Some acetophenone - aroyl Hydrazone compounds have been studied by the inhibition of copper corcosion in 3N nitric acid solution. The structure of some acetophenone - aroyl iydriron" compounds were optimized and calculated by using the ZINDO/I method of the quantum chemical program HyperChem 7.0, Results of the above calculation is coordinated with inhibition eficiency (P) that is dertermined by experimentation and both are apptiei to Statgraphic software to carry out linear regression.